GI2025 at CSUCI Priority 5, Fall '22 Report (2022)
The CSU system's Graduation Goals 2025 initiative has charged each campus within the system to close equity gaps and help more students succeed. As part of this effort, and in alignment with Equity Priority 5, CSU Channel Islands has identified courses that substantially impact a large number of students that serve as critical opportunities to improve learning outcomes and have at least one equity gap.